2017
DOI: 10.5114/ceh.2017.70281
|View full text |Cite
|
Sign up to set email alerts
|

Ombitasvir/paritaprevir/ritonavir + dasabuvir ± ribavirin for treatment of chronic hepatitis C 1 genotype in the Republic of Belarus

Abstract: Aim of the studyAim of the study is to evaluate real-world efficacy of the ombitasvir/ paritaprevir/ ritonavir + dasabuvir ± ribavirin for treatment of chronic hepatitis C 1 genotype.Material and methodsThe study included 27 patients according to inclusion criteria. Main laboratory studies were performed in all patients at the baseline and during the treatment.ResultsEfficacy of the antiviral therapy was assessed by measuring the SVR12 and the SVR24 along with measuring of viral load during the treatment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
3
1
0
Order By: Relevance
“…AMBER was the first RWE study in the world with this therapeutic regimen to demonstrate a high SVR rate and an excellent safety profile, even in patients with cirrhosis, a history of interferon-based therapy failure, and after liver transplantation [8]. Further studies published by other authors confirmed our findings from the 12-week post-treatment assessment [9][10][11][12][13][14]. A further two-year follow-up of patients participating in the AMBER program confirmed the persistence of the virological response, which was accompanied by a significant improvement in the main functional indicators including, in particular, a reduction in liver stiffness (LS).…”
Section: Introductionsupporting
confidence: 82%
“…AMBER was the first RWE study in the world with this therapeutic regimen to demonstrate a high SVR rate and an excellent safety profile, even in patients with cirrhosis, a history of interferon-based therapy failure, and after liver transplantation [8]. Further studies published by other authors confirmed our findings from the 12-week post-treatment assessment [9][10][11][12][13][14]. A further two-year follow-up of patients participating in the AMBER program confirmed the persistence of the virological response, which was accompanied by a significant improvement in the main functional indicators including, in particular, a reduction in liver stiffness (LS).…”
Section: Introductionsupporting
confidence: 82%
“…Safety evaluation demonstrated mostly mild adverse events, which rarely led to treatment discontinuation . Efficacy and safety results from this study were shortly confirmed with other RWE studies …”
Section: Introductionsupporting
confidence: 80%
“…12 Efficacy and safety results from this study were shortly confirmed with other RWE studies. [13][14][15][16] The sustained virologic response in the AMBER study was assessed 12 weeks after the end of treatment (EOT), which is the current standard efficacy assessment endpoint. 17,18 However, longterm outcomes of successful treatment with DAA need further studies, because available up-to-now data were usually not collected in a fixed period on post-treatment follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a significant improvement of evolution of functional liver tests (ALT, AST) was observed during the 12 weeks of treatment compared with the baseline. This is confirmed by both Phase III clinical studies and real world studies [17,18,19]. The total bilirubin level increased significantly during the 12 weeks of treatment, with a peak in week 4, but returned to normal after 12 weeks following treatment completion.…”
Section: Discussionsupporting
confidence: 60%